MENUJU SEKOLAH ADIWIYATA: IMPLEMENTASI PENDIDIKAN LINGKUNGAN HIDUP DI SDN 3 BANGUNSARI - Syaikudin, Ahmad (Journal Of Islamic Elementary School (JIES), 2016)
Ecology education is effort to conserve ecology by teaching it formally. Ecology education is not a course independently. But it can be integrated with the other learning course in school. The aim of this research is to know carrying out of 4 execution standarts of ecology education on SDN 3 Bangunsari Ponorogo to be sekolah adiwiyata. This research is descriptive qualitative research to describe four program standart in adiwiyata. Data collection method that is used in this research is questionare, observation, and documentation. The resulths indicate that: 1) the implementation of Adiwiyata program on SDN 3 Bangunsari Ponorogo has run well by adiwiyata 4 program standarts has been fulfilled, 2) The instance has carried out its duty and authority well by motivating and supporting for running well annually. It is discovered little obstacle especially concerning with finance. However, school has made a strategic action too overcome that obstacle.